Metaverso y Non-Fungible Tokens (NFTs): Retos y Oportunidades desde la perspectiva del derecho de marcas - Alvarado Bayo, María del Carmen (2022)
The rapid development of the metaverse and its constituent components brings with it a host of challenges and opportunities covering a myriad of aspects. However, there is one field that has a special intersection with the new form of interaction proposed by the metaverse. We refer to property that is valuable both physically and virtually: intellectual property. Specifically, within the field of intellectual property, we will refer to the role played by trademarks in the metaverse and in the so-called Non-fungible tokens (NFTs), considering-particularly-the challenges and opportunities presented by this new virtual reality.